HISTOGENESIS OF SOLID TYPE DUCT CANCER OF A WOMAN’S BREAST GLAND - Nikolenko, D.Ye.; Кokovska O.V. (World of Medicine and Biology, 2024)
In Ukraine, the development of ductal cancer of the mammary gland continues to be a growing problem for the health of women, not only of the elderly but also of young age, and the cause of death in 18–20 % of cases. Non-invasive forms of cancer, which account for 5–8 % of cases, are associated with the proliferative process in the alveolar part of the gland. The structural and functional organization of the epithelium in the terminal duct of the gland on the autopsy material of women of reproductive age who died from infectious diseases was studied, as well as the solid type of ductal cancer of the gland was retrospectively identified, according to the WHO classification (2003); histological, histochemical, immunohistochemical methods were applied (markers p63, bcl-2, α-sma, VEGF from DakoCytomation) with karyometric analysis. The paper presents a new theoretical justification and solution to the topical issue of histogenesis of solid breast cancer based on a comparison with the epithelium of the terminal part of the duct – the acinus-button. The histogenesis of cancer with an extreme degree of cataplasia associated with the terminal part of the duct is presented.